Penerapan Model Pembelajaran Cooperative Learning Tipe Jigsaw dalam Upaya Meningkatkan Hasil Belajar - Maisura; Eka Agustina (Jurnal Ilmiah Literasi Indonesia, 2025)
This study aims to improve learning outcomes by implementing the jigsaw cooperative learning model for ninth grade students at SMP N 1 Sakti in the 2024/2025 academic year. The subjects of this study were 30 ninth grade students at SMP N 1 Sakti. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, action, observation, reflection, and revision stages. Data collection techniques use observation and tests. Based on the research results, it can be concluded that there was an improvement in the learning outcomes of ninth-grade students at SMP N 1 Sakti after the implementation of the Jigsaw cooperative learning model in social studies. This can be seen in the initial conditions, where the average score was 52.5, with a maximum score of 70. In Cycle I, the average score was 60.69, with a maximum score of 90. In Cycle II, the average score was 74.14, with a maximum score of 100. Learning completion increased, from 48.28% in the initial conditions, to 65.22% in Cycle I, and 89.65% in Cycle II.